Deep learning-based waste classification system for efficient waste management - Nakib, Abdullah Al; Talukder, Md. Nayem; Majumder, Chinmoy; Biswas, Soptorshi; Hassan, Jabid (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.